Unified description of thermal and nonthermal laser-induced ultrafast structural changes in materials - Bernd Bauerhenne; Martin E. Garcia (Scientific Reports)
Abstract The ultrafast ionic dynamics in solids induced by intense femtosecond laser excitation are controlled by two fundamentally different yet interrelated phenomena. First, the substantial generation of hot electron-hole pairs by the laser pulse modifies the interatomic bonding strength and characteristics, inducing nonthermal ionic motion. Second, incoherent electron-ion collisions facilitate thermal equilibration between electrons and ions, achieving a uniform temperature on a picosecond timescale. This article presents a unified theoretical description that effectively integrates both processes. Our method is adaptable for use in both ab-initio simulations and extensive molecular dynamics simulations, extending the conventional two-temperature model to incorporate molecular dynamics equations of motion. To demonstrate the efficacy of our approach, we apply it to the laser excitation of silicon thin films. Our simulations closely match experimental observations, accurately reproducing the temporal evolution of the Bragg peaks.